We’re All the Same: Collective Narcissists’ Cross-National Support for Putin and Russian Military Attacks - Genavee Brown; Gaëlle Marinthe (International Review of Social Psychology, 2024)
National narcissism is associated with support for nationalist and anti-democratic leaders and decisions in one’s own country. We hypothesize that it might also relate to more favorable judgments of outgroup nationalist leaders and actions, even if the latter may pose a threat to the ingroup. Using the context of the Russian attack on Ukraine, we hypothesize that people with a higher level of national narcissism would be more supportive of Russian attacks, Russian President Vladimir Putin, and the Russian people. This may be due to a higher perception of belief similarity to Putin and Russians. We also considered the moderating role of the explicit target of the attack (Ukraine vs. ingroup). We tested our hypotheses in two studies (Study 1: N = 339 French; Study 2: N = 400 Americans). In both studies, national narcissism was related to a judgment of the attack (on Ukraine or the ingroup) as less immoral and to a better opinion of Putin. These effects were mediated by perceived belief similarity. In both studies however, these less negative judgments of the attack and of Putin did not extend to Russian people. Our results highlight that national narcissists are inclined to support a nationalist outgroup leader and their violent actions, although these may ultimately harm the ingroup.